2007
DOI: 10.1007/s10661-007-9854-4
|View full text |Cite
|
Sign up to set email alerts
|

Implications of climate change for evaporation from bare soils in a Mediterranean environment

Abstract: The purpose of this study was to predict quantitative changes in evaporation from bare soils in the Mediterranean climate region of Turkey in response to the projections of a regional climate model developed in Japan (hereafter RCM). Daily RCM data for the estimation of reference evapotranspiration (ETr) and soil evaporation were obtained for the periods of 1994--2003 and 2070--2079. Potential evaporation (Ep) from bare soils was calculated using the Penman-Monteith equation with a surface resistance of zero. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
2
19
1
Order By: Relevance
“…E p rates were lower than ET r values (E p =0.75×ET r ), because the evaporation from bare soils depended not only on the atmospheric conditions but also on soil properties. Aydin et al (2008) found a similar relationship between E p and ET r . Kroes et al (1999) reported that ET r rates could be multiplied by a coefficient value of 0.5 to 1.5 to obtain E p .…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…E p rates were lower than ET r values (E p =0.75×ET r ), because the evaporation from bare soils depended not only on the atmospheric conditions but also on soil properties. Aydin et al (2008) found a similar relationship between E p and ET r . Kroes et al (1999) reported that ET r rates could be multiplied by a coefficient value of 0.5 to 1.5 to obtain E p .…”
Section: Resultsmentioning
confidence: 56%
“…In order to overcome such problems, Aydin (2008) proposed an interactive way (called E-DiGOR 485 model by the author) for predicting daily actual soil evaporation, soil water storage and drainage rates, since these components are strongly interdependent. The applicability of E-DiGOR model to a wide range of environments has been tested by different researchers using field-based measurements (Aydin, 2008;Aydin et al, 2008;Kurt, 2011). Similarly, the model had been successfully applied to different environmental conditions in Turkey, Japan and Sri Lanka (Aydin et al, 2005;Onder et al, 2009;Aydin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Through evaporation, soil water comes into the atmosphere to form cloud, which is a significant source of atmospheric water. At the same time, soil evaporation can lead to soil water loss [1][2][3][4][5][6]. According to the estimation, this water loss can amount to 50% of the total soil water or more during a normal growing season [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…First, calcic nodules can modify soil configuration and surface properties, leading to the changes of surface roughness and soil reflectivity that is closely linked to soil thermal property [12]. Second, calcic nodules have some effect on water allocation between soil and calcic nodules [12,13], and finally initiates soil moisture [1,2], which to some extent dominates soil evaporation [14]. In addition, calcic nodules can enhance soil water holding capacity and reduce water vapor sorption between soil surface and atmosphere especially as calcic nodules mulching soil surface [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation